2018
DOI: 10.1152/physiolgenomics.00039.2017
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of microRNAs for the treatment of renal fibrosis and CKD

Abstract: Chronic kidney disease (CKD), defined as reduced glomerular filtration rate, is increasingly becoming a major public health issue. At the histological level, renal fibrosis is the final common pathway leading to end-stage renal disease, irrespective of the initial injury. According to this view, antifibrotic agents should slow or halt the progression of CKD. However, due to multiple overlapping pathways stimulating fibrosis, it has been difficult to develop antifibrotic drugs that delay or reverse the progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 133 publications
(190 reference statements)
1
74
0
Order By: Relevance
“…Unfortunately, our findings are in line with those of many other investigators that aimed at validating urine biomarkers of kidney damage [46]. Arguably, blood-based biomarkers [47], microRNAs reflecting renal fibrosis [48], and/or advanced kidney imaging strategies [49] might be better suited to capture abnormalities in renal mechanisms due to structural changes with LN chronicity.…”
Section: Discussionsupporting
confidence: 86%
“…Unfortunately, our findings are in line with those of many other investigators that aimed at validating urine biomarkers of kidney damage [46]. Arguably, blood-based biomarkers [47], microRNAs reflecting renal fibrosis [48], and/or advanced kidney imaging strategies [49] might be better suited to capture abnormalities in renal mechanisms due to structural changes with LN chronicity.…”
Section: Discussionsupporting
confidence: 86%
“…miRNAs have emerged as powerful regulators of fibrotic processes in the kidney (55,56). Thus, Gomez et al identified 24 miRNAs that were commonly upregulated both in human CKD and in animal models of kidney injury, suggesting a "fibrotic" miRNA signature in the kidney (18).…”
Section: Discussionmentioning
confidence: 99%
“…1 When renal fibrosis occurs, most of the patients will develop to chronic kidney disease (CKD), following with end-stage renal disease (ESRD). 4 In that situation, transplantation is the only effective therapeutic strategy. 5 In addition, it has been reported that patients with CKD account for 10% of the world's population.…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition, it has been reported that patients with CKD account for 10% of the world's population. 4 Therefore, novel effective strategy that inhibits progression of renal fibrosis caused by diabetic nephropathy is of great importance.…”
Section: Introductionmentioning
confidence: 99%